Thermoplastic resin composition and molded article manufactured therefrom
By reasonably preparing components such as acrylic rubber-modified graft copolymers, silicone-acrylate composite rubber-modified graft copolymers, the existing thermoplastic resins lack impact resistance and heat resistance, and high-performance thermoplastic resin compositions and molded products are achieved.
Patent Information
- Application Number
- CN202380057706.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-18
- Publication Date
- 2025-03-14
AI Technical Summary
Existing thermoplastic resins, such as ASA/PMMA alloy resins, lack impact resistance and heat resistance, and the transparency and colorability of the molded articles will be reduced after using a heat-resistant enhancer.
A thermoplastic resin composition is employed, including acrylic rubber-modified graft copolymers, silicone-acrylate composite rubber-modified graft copolymers, polyalkyl (meth)acrylate resins, silicone modified polyesters, anthraquinone dyes and free radical scavengers having a weight average molecular weight of more than or the like.
The thermoplastic resin composition is achieved with excellent scratch resistance, weather resistance and color resistance, and by improving impact resistance and flowability, the overall performance of the molded product is improved.
Smart Images

Figure BDA0005260997790000021 
Figure BDA0005260997790000031 
Figure BDA0005260997790000081
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition and a molded article produced therefrom. Background Art
[0002] Recently, thermoplastic resins widely used in electrical / electronic products, automobiles, building materials, leisure products, etc. have rapidly replaced the fields of conventional glass or metal. Accordingly, the demand for thermoplastic resins capable of achieving improved impact resistance, weather resistance, molding processability, and high-quality appearance is increasing.
[0003] Acrylonitrile-butadiene-styrene copolymer resin (hereinafter, ABS resin) widely used as a thermoplastic resin includes chemically unstable double bonds in the rubber component, and thus the rubber component can be easily aged by ultraviolet rays. Accordingly, ABS resin has poor weather resistance and light resistance, so if left outdoors for a long time, it is easy to discolor and deteriorate in physical properties over time, making it unsuitable for outdoor use exposed to sunlight.
[0004] In contrast, acrylonitrile-styrene-acrylate copolymer resin (hereinafter, ASA resin) uses a chemically stable acrylate rubber polymer instead of a butadiene rubber polymer as a rubber component, and thus is known to solve the problem of discoloration and performance degradation of the ABS resin due to aging of the rubber component caused by ultraviolet (UV) rays. In addition, the ASA resin has improved plasticity, chemical resistance, thermal stability, etc., as well as weather resistance and light resistance.
[0005] Recently, in accordance with the trend towards environmental friendliness, the demand for non-coating thermoplastic resins that can be used without a coating process has increased. Since non-coating thermoplastic resins are used as non-coating molded products, they must have excellent scratch resistance, coloring, impact resistance, and weather resistance, and recently, as the level of performance requirements increases, attempts to apply ASA / PMMA alloy resins, which are ASA resins mixed with polymethyl methacrylate resins (hereinafter, PMMA resins), are also increasing.
[0006] However, compared with ASA resin, ASA / PMMA alloy resin lacks impact resistance and heat resistance. In particular, when ordinary heat-resistant reinforcing agents are used to supplement heat resistance, the transparency and colorability of the molded product are reduced due to the refractive index difference between the continuous phase (matrix) and the dispersed phase (domain), so it may be necessary to use an excessive amount of colorant (such as pigment or dye) to color the molded product.
[0007] Therefore, there is a need to develop a thermoplastic resin composition having excellent scratch resistance, weather resistance, and colorability. Summary of the invention
[0008]
Technical issues
[0009] Embodiments provide a thermoplastic resin composition having excellent scratch resistance, weather resistance, and colorability, and a molded article made therefrom.
[0010]
Technical solution
[0011] According to an embodiment, the thermoplastic resin composition includes 100 parts by weight of a base resin including: (A) 10 to 15 wt% of an acrylic rubber-modified graft copolymer, (B) 10 to 30 wt% of a silicone-acrylate composite rubber-modified graft copolymer, and (C) 60 to 80 wt% of a polyalkyl (meth)acrylate resin, and (D) 0.5 to 3 parts by weight of a siloxane-modified polyester based on the above base resin; (E) 0.1 to 1 parts by weight of an anthraquinone dye; and (F) 0.1 to 1 parts by weight of a radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol.
[0012] (A) The acrylic rubber-modified graft copolymer may include a core including an acrylic ester rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0013] The average particle size of the acrylic rubber polymer may be 200 to 300 nm.
[0014] (A) The acrylic rubber modified graft copolymer may include a butyl acrylate-styrene cross-linked copolymer core, and a shell formed by grafting polymethyl methacrylate (PMMA) onto the core.
[0015] (B) The silicone-acrylate composite rubber-modified graft copolymer may include a core comprising a silicone-acrylate composite rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0016] The average particle size of the silicone-acrylate composite rubber-like polymer may be 100 to 200 nm.
[0017] (B) The silicone-acrylate composite rubber-modified graft copolymer may include an acrylate-silicone cross-linked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0018] (C) The polyalkyl (meth)acrylate resin may be a polymethyl methacrylate (PMMA) resin.
[0019] (D) The siloxane-modified polyester may include a structural unit represented by Chemical Formula 1:
[0020] [Chemical formula 1]
[0021]
[0022] (In Chemical Formula 1,
[0023] R 1 and R 6 are each independently hydrogen, hydroxy or methyl,
[0024] R 2 , R 3 , R 4 and R 5 Each is independently a C1-C10 alkylene group,
[0025] R 7 , R 8 , R 9 and R 10 are each independently a C1-C10 alkyl group or a C6-C20 aryl group, and
[0026] m1, m2 and n are each independently an integer greater than or equal to 1).
[0027] (F) The radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol may include a structure represented by Chemical Formula 2:
[0028] [Chemical formula 2]
[0029]
[0030] (In Chemical Formula 2, m is an integer of 2 to 20).
[0031] The thermoplastic resin composition may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, mold release agents, heat stabilizers, antioxidants, ultraviolet (UV) stabilizers, pigments, and dyes.
[0032] In another embodiment, a molded article made from the thermoplastic resin composition is provided.
[0033] The molded article may have a lightness (L*) of less than or equal to 2.0 as measured in specular excluded (SEC) mode on a 2.5 mm thick sample according to ASTM E308.
[0034] The molded article may have a color change (ΔE) of less than or equal to 3.0 before and after a weathering test as measured by irradiating the molded article with an energy of 4,500 kJ according to SAE J 1960.
[0035] The molded article may have a lightness change (ΔL) of less than or equal to 2.0 before and after the scratch resistance evaluation as measured using an Erichsen scratch hardness tester 430P-I.
[0036]
Beneficial Effects
[0037] A thermoplastic resin composition having excellent scratch resistance, weather resistance and colorability, and a molded article produced therefrom can be provided. DETAILED DESCRIPTION
[0038] Hereinafter, embodiments of the present invention are described in detail. However, these embodiments are exemplary, and the present disclosure is not limited thereto.
[0039] In the present specification, unless otherwise mentioned, "copolymerization" means block copolymerization, random copolymerization or graft copolymerization, and "copolymer" means block copolymer, random copolymer or graft copolymer.
[0040] In the present specification, unless otherwise mentioned, the average particle size of the rubbery polymer refers to a volume average diameter, and means a Z-average particle size measured using a dynamic light scattering analysis instrument.
[0041] In this specification, unless otherwise mentioned, the weight average molecular weight is measured by dissolving a powder sample in an appropriate solvent and then subjecting it to gel permeation chromatography (GPC) using 1200 series manufactured by Agilent Technologies (the standard sample is polystyrene manufactured by Shodex).
[0042] The thermoplastic resin according to the embodiment includes 100 parts by weight of a base resin including: (A) 10 to 15 wt% of an acrylic rubber modified graft copolymer, (B) 10 to 30 wt% of a silicone-acrylate composite rubber modified graft copolymer, and (C) 60 to 80 wt% of a polyalkyl (meth) acrylate resin, and (D) 0.5 to 3 parts by weight of a siloxane-modified polyester based on the above base resin; (E) 0.1 to 1 parts by weight of an anthraquinone dye; and (F) 0.1 to 1 parts by weight of a radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol.
[0043] Hereinafter, each component of the thermoplastic resin composition is described in detail.
[0044] (A) Acrylic rubber modified graft copolymer
[0045] The thermoplastic resin composition according to an embodiment includes (A) an acrylic rubber-modified graft copolymer. The (A) acrylic rubber-modified graft copolymer plays a role in enhancing various physical properties of the thermoplastic resin composition, such as impact resistance, mechanical properties, and appearance properties.
[0046] In an embodiment, the (A) acrylic rubber-modified graft copolymer may include a core including an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0047] (A) The acrylic rubber-modified graft copolymer can be prepared by any method known to those skilled in the art.
[0048] The preparation method may be a conventional polymerization method, for example, emulsion polymerization, suspension polymerization, solution polymerization or bulk polymerization, etc. As a non-limiting example, it may be prepared by preparing an acrylic rubber polymer, and graft-polymerizing at least one selected from a (meth) acrylic acid ester compound, an aromatic vinyl compound and a vinyl cyanide compound onto a core formed of at least one layer of the acrylic rubber polymer to form a shell of at least one layer.
[0049] The acrylic ester rubber-like polymer may be a cross-linked polymer prepared using an acrylic ester compound as a main monomer. The acrylic ester compound may be, for example, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, or a combination thereof.
[0050] The acrylate compound can be copolymerized with one or more other free radical polymerizable monomers. When copolymerized, the amount of the one or more other free radical polymerizable monomers can be 5 to 30 wt%, such as 10 to 20 wt%, based on the total weight of the acrylate rubber polymer.
[0051] The average particle size of the acrylic rubber-like polymer may be 200 to 300 nm. Within the above average particle size range, the thermoplastic resin composition may have improved mechanical properties such as impact resistance and tensile strength and colorability.
[0052] The (meth)acrylate compound included in the shell may be at least one selected from methacrylate, acrylate, methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0053] The aromatic vinyl compound included in the shell may be at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, chlorostyrene, vinyltoluene, and vinylnaphthalene, but is not limited thereto.
[0054] The vinyl cyanide compound included in the shell may be at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and fumaronitrile, but is not limited thereto.
[0055] In an embodiment, when a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound is graft-polymerized onto a core including an acrylic rubber-like polymer to form a shell, the shell may be a copolymer of a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound in a weight ratio of 1:1 to 4:1 (e.g., 1:1 to 3:1).
[0056] In an embodiment, (A) the acrylic rubber-modified graft copolymer may include 40 to 80 wt % of an acrylic ester rubber-like polymer. Within the above weight range, weather resistance and impact resistance of the thermoplastic resin composition may be improved.
[0057] In an embodiment, the (A) acrylic rubber modified graft copolymer may include a butyl acrylate-styrene cross-linked copolymer core and a shell formed by grafting polymethyl methacrylate (PMMA) onto the core.
[0058] In an embodiment, based on 100 wt % of the base resin, the content of (A) the acrylic rubber modified graft copolymer may be 10 to 15 wt %, such as 10 to 12 wt %, such as 12 to 15 wt %. Within the above wt % range, the thermoplastic resin composition may have excellent impact resistance and scratch resistance.
[0059] (B) Silicone-acrylate composite rubber modified graft copolymer
[0060] The thermoplastic resin composition according to the embodiment includes (B) a silicone-acrylate composite rubber-modified graft copolymer. The (B) silicone-acrylate composite rubber-modified graft copolymer imparts excellent impact resistance to the thermoplastic resin composition. The (B) silicone-acrylate composite rubber-modified graft copolymer may include a core including a silicone-acrylate composite rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0061] (B) The silicone-acrylate composite rubber-modified graft copolymer may be prepared by using emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, etc. As a non-limiting example, it may be prepared by preparing a silicone-acrylate composite rubber-like polymer, and graft-polymerizing a monomer mixture including at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto a core formed of at least one layer of the silicone-acrylate composite rubber-like polymer to form a shell of at least one layer.
[0062] The silicone-acrylate composite rubbery polymer may be a cross-linked copolymer of an acrylate compound and a silicone compound, or a mixture of an acrylate rubbery polymer and a silicone rubbery polymer.
[0063] The acrylic rubber polymer may be a cross-linked polymer prepared by using an acrylic compound as a main monomer. The acrylic compound may be, for example, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, or a combination thereof, but is not limited thereto.
[0064] The silicone-based rubber-like polymer may be a cross-linked polymer prepared by using a silicone-based compound as a main monomer. The silicone-based compound may be, for example, dimethylsiloxane, methylphenylsiloxane, methylvinylsiloxane, or a combination thereof, but is not limited thereto.
[0065] The average particle size of the silicone-acrylate composite rubber-like polymer may be 100 to 200 nm, for example, 120 to 180 nm. Within the above average particle size range, the thermoplastic resin composition may have improved impact resistance and colorability.
[0066] In the silicone-acrylate composite rubbery polymer, a weight ratio of the component derived from the acrylate compound to the component derived from the silicone compound may be 95:5 to 85:15, for example 95:5 to 90:10. Within this range, the thermoplastic resin composition may have improved impact resistance and colorability.
[0067] The silicone-acrylate composite rubber-like polymer may be included in an amount of 20 to 60 wt %, for example 30 to 60 wt %, for example 40 to 60 wt %, based on 100 wt % of the (B) silicone-acrylate composite rubber-modified graft copolymer.
[0068] The (meth)acrylate compound included in the shell may be at least one selected from methacrylate, acrylate, methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0069] The aromatic vinyl compound included in the shell may be at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, chlorostyrene, vinyltoluene, and vinylnaphthalene, but is not limited thereto.
[0070] The vinyl cyanide compound included in the shell may be at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and fumaronitrile, but is not limited thereto.
[0071] In an embodiment, when a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound is graft-polymerized onto a silicone-acrylate composite rubbery polymer to form a shell, the shell may be a copolymer of a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound in a weight ratio of 1:1 to 4:1 (e.g., 1:1 to 3:1).
[0072] In an embodiment, the (B) silicone-acrylate composite rubber modified graft copolymer may include an acrylate-silicone cross-linked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0073] In an embodiment, based on 100wt% of the base resin, the content of the (B) silicone-acrylate composite rubber-modified graft copolymer may be greater than or equal to 10wt%, such as greater than or equal to 15wt%, such as less than or equal to 30wt%, such as less than or equal to 25wt%, such as 10 to 30wt%, such as 15 to 25wt%. Within the above weight range, the thermoplastic resin composition may have excellent impact resistance, fluidity and colorability.
[0074] (C) Polyalkyl (meth)acrylate resin
[0075] The thermoplastic resin composition according to an embodiment includes (C) a polyalkyl (meth)acrylate resin. The (C) polyalkyl (meth)acrylate resin may impart scratch resistance to the thermoplastic resin composition.
[0076] (C) The polyalkyl (meth)acrylate resin can be obtained by polymerizing an alkyl (meth)acrylate compound by a known polymerization method such as suspension polymerization, bulk polymerization or emulsion polymerization.
[0077] The alkyl (meth)acrylate-based compound may be at least one selected from methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0078] The (C) polyalkyl (meth)acrylate resin may have a glass transition temperature of 100 to 150°C, or for example, 110 to 130°C.
[0079] (C) The polyalkyl (meth)acrylate resin may have a weight average molecular weight of 50,000 g / mol to 200,000 g / mol, specifically 70,000 g / mol to 150,000 g / mol. When the above range is satisfied, the thermoplastic resin composition may exhibit excellent scratch resistance and fluidity.
[0080] In embodiments, the (C) polyalkyl(meth)acrylate resin may be a polymethyl methacrylate (PMMA) resin.
[0081] The (C) polyalkyl (meth) acrylate resin may be included in an amount of 60 wt % or more, such as 65 wt % or more, such as 80 wt % or less, such as 75 wt % or less, such as 60 to 80 wt %, such as 60 to 75 wt %, such as 65 to 75 wt %, based on 100 wt % of the base resin. Within the above range, the thermoplastic resin composition may have improved scratch resistance.
[0082] (D) Siloxane-modified polyester
[0083] The thermoplastic resin composition according to an embodiment includes (D) siloxane-modified polyester. (D) Siloxane-modified polyester may improve scratch resistance of the thermoplastic resin composition.
[0084] Polymethyl methacrylate (PMMA) resin, which is commonly used to improve scratch resistance, has excellent scratch resistance due to high transmittance, surface gloss, and excellent rigidity. However, the problem with polymethyl methacrylate resin is that it has low impact strength compared to other plastic materials, making it difficult to apply to applications requiring impact resistance. Therefore, an appropriate impact modifier should be used to improve impact resistance.
[0085] However, since the introduction of impact modifiers has the disadvantage of reducing surface hardness and scratch resistance when used for automobile exteriors, electronic equipment housings, etc., serious appearance quality problems such as external contaminants, scratches, and scratches caused by users may occur, and during product production, scratches caused by workers may increase the product defect rate, thereby leading to an increase in production costs. In addition, if a protective film or the like is used to prevent scratches, this may increase manufacturing costs and have a negative impact on product prices.
[0086] The present invention aims to solve the above problems and can provide a thermoplastic resin composition having excellent scratch resistance and improved impact resistance and fluidity by introducing (D) a siloxane-modified polyester into a base resin comprising (A) to (C).
[0087] (D) The siloxane-modified polyester can be represented by Chemical Formula 1:
[0088] [Chemical formula 1]
[0089]
[0090] In Chemical Formula 1,
[0091] R 1 and R 6are each independently hydrogen, hydroxy or methyl,
[0092] R 2 , R 3 , R 4 and R 5 Each is independently a C1-C10 alkylene group,
[0093] R 7 , R 8 , R 9 and R 10 are each independently a C1-C10 alkyl group or a C6-C20 aryl group, and
[0094] m1, m2 and n are each independently an integer greater than or equal to 1).
[0095] In an embodiment, R of Chemical Formula 1 3 and R 4 can be independently C1-C3 alkylene, R 2 and R 5 can be independently C3-C5 alkylene, R 7 , R 8 , R 9 and R 10 Each may independently be a C1-C4 alkyl group, and (m1+m2):n may be 1.5:3 to 2:3.
[0096] Based on 100 parts by weight of the base resin, the content of (D) siloxane-modified polyester may be 0.5 to 3 parts by weight, such as 1 to 3 parts by weight, such as 1 to 2 parts by weight. Within the above weight range, the scratch resistance and impact resistance of the thermoplastic resin composition may be improved.
[0097] (E) Anthraquinone dyes
[0098] The thermoplastic resin composition according to an embodiment may include (E) an anthraquinone-based dye. The (E) anthraquinone-based dye may allow the thermoplastic resin composition to exhibit a black color.
[0099] The (E) anthraquinone-based dye may be a compound including a component having a structure represented by Chemical Formula 3 in an amount of greater than or equal to 50 wt %.
[0100] [Chemical formula 3]
[0101]
[0102] In an embodiment, a dispersant may be used together with anthraquinone-based dye to disperse it in the thermoplastic resin composition. Specifically, the dye may be used by pre-surface treatment with a dispersant or by adding the dispersant together with the dye when preparing the thermoplastic resin composition.
[0103] The dispersant may be a nonionic dispersant, anionic dispersant, cationic dispersant, or the like.
[0104] The (E) anthraquinone-based dye may be included in an amount of 0.1 to 1 part by weight, for example 0.1 to 0.8 parts by weight, based on 100 parts by weight of the base resin.
[0105] (F) a free radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol
[0106] The thermoplastic resin composition according to an embodiment may include (F) a radical scavenger having a weight average molecular weight of greater than or equal to 2,000 g / mol, and the radical scavenger may play a role in improving weather resistance of the thermoplastic resin composition of the present invention.
[0107] The radical scavenger may include a compound having a radical scavenging ability, such as a hindered amine compound, a hindered phenol compound, or a mixture of two or more thereof.
[0108] In an embodiment, (F) the radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol may include a structure represented by Chemical Formula 2.
[0109] [Chemical formula 2]
[0110]
[0111] (In Chemical Formula 2, m is an integer of 2 to 20).
[0112] (F) The radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol may have a weight average molecular weight of 2,000 to 10,000 g / mol, for example, 2,000 to 5.000 g / mol, for example, 2,000 to 3,000 g / mol.
[0113] The (F) radical scavenger having a weight average molecular weight of greater than or equal to 2,000 g / mol may be included in an amount of 0.1 to 1 part by weight, for example 0.1 to 0.8 parts by weight, based on 100 parts by weight of the base resin. Within the above weight range, the thermoplastic resin composition may have excellent weather resistance.
[0114] (G) Additives
[0115] The thermoplastic resin composition according to an embodiment may further include one or more additives, in addition to components (A) to (F), which are necessary to balance properties while not causing deterioration of other characteristics or depending on the final use of the thermoplastic resin composition.
[0116] Specifically, the additive may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, mold release agents, thermal stabilizers, antioxidants, ultraviolet (UV) stabilizers, pigments, and dyes.
[0117] These additives may be appropriately included unless the characteristics of the thermoplastic resin composition are deteriorated, and specifically, the content of these additives is less than or equal to about 20 parts by weight based on 100 parts by weight of the base resin, but is not limited thereto.
[0118] On the other hand, the thermoplastic resin composition of the embodiment may be mixed with other resins or other rubber components.
[0119] On the other hand, another embodiment provides a molded article manufactured using the thermoplastic resin composition according to the embodiment. The molded article can be manufactured by various methods known in the related art (for example, by injection molding, extrusion molding, etc. using the thermoplastic resin composition).
[0120] The molded article may have a lightness (L*) of less than or equal to 2.0, less than or equal to 1.9, or less than or equal to 1.8, measured in specular excluded (SEC) mode according to ASTM E308 on a 2.5 mm thick sample.
[0121] The molded article may have a color change (ΔE) of less than or equal to 3.0, less than or equal to 2.8, less than or equal to 2.6, less than or equal to 2.4, less than or equal to 2.2, less than or equal to 2.0 before and after weathering testing as measured by irradiating the molded article with 4,500 kJ of energy in accordance with SAE J 1960.
[0122] The molded article may have a lightness change (ΔL) of less than or equal to 2.0, less than or equal to 1.8, less than or equal to 1.6, less than or equal to 1.4, less than or equal to 1.2, or less than or equal to 1.0 before and after the scratch resistance evaluation as measured using an Erichsen scratch hardness tester 430P-I.
[0123] [Implementation Methods of the Invention]
[0124] Hereinafter, preferred embodiments of the present invention will be described. However, these embodiments are not to be construed as limiting the scope of the present invention in any case.
[0125] Examples 1 to 4 and Comparative Examples 1 to 7
[0126] According to the content ratio of each component shown in Table 1, thermoplastic resin compositions according to Examples 1 to 4 and Comparative Examples 1 to 7 were prepared, respectively.
[0127] The components shown in Table 1 were mixed in a conventional mixer, and then, extruded at a barrel temperature of about 230° C. by using a twin-screw extruder (L / D=29, Φ=45 mm) to prepare each thermoplastic resin composition in the form of pellets. Each thermoplastic resin composition pellet was dried in a dehumidifying dryer at about 80° C. for about 4 hours, and then, a sample for measuring physical properties was manufactured by using a 6-ounce injection molding machine and setting a cylinder temperature of about 230° C. and a mold temperature of about 60° C. The measured properties are shown in Table 2.
[0128] In Table 1, components (A) to (C) are respectively expressed as wt% based on the total weight of components (A) to (C), and components (D) to (F) are expressed as parts by weight based on 100 parts by weight of the total weight of components (A) to (C).
[0129] (Table 1)
[0130]
[0131] Each component shown in Table 1 is described in detail as follows.
[0132] (A) Acrylic rubber modified graft copolymer
[0133] The core-shell structure graft copolymer includes a core of about 60 wt% of a butyl acrylate-styrene crosslinked copolymer having an average particle size of about 250 nm and a shell grafted onto the core with polymethyl methacrylate (product name: Kane M-210, manufacturer: Kaneka Corporation).
[0134] (B) Silicone-acrylate composite rubber modified graft copolymer
[0135] The core-shell graft copolymer includes a core of about 60 wt% of an acrylic acid ester compound-silicone compound crosslinked copolymer having an average particle size of about 150 nm and a shell grafted onto the core with styrene and acrylonitrile in a weight ratio of about 2:1 (product name: Metablen TM SX-006, manufacturer: Mitsubishi Chemical Corporation).
[0136] (C) Polyalkyl (meth)acrylate resin
[0137] A polymethyl methacrylate (PMMA) resin (product name: VH, manufacturer: Lotte Chemical Co., Ltd.) having a weight average molecular weight of about 100,000 g / mol was used.
[0138] (D) Siloxane-modified polyester
[0139] Use manufactured by Evonik Industries AG H-Si 6441P.
[0140] (E-1) Anthraquinone dyes
[0141] A dye including 50 wt % or more of a component having a structure represented by Chemical Formula 3 is used.
[0142] (E-2) Carbon black
[0143] Made by Orion Engineered Carbons 50L.
[0144] (E-3) Acridine dyes
[0145] Using a dye including 50 wt% or more of a component having a structure represented by Chemical Formula 4:
[0146] [Chemical formula 4]
[0147]
[0148] (E-4) Phthalocyanine dyes
[0149] Using a dye including 50 wt% or more of a component having a structure represented by Chemical Formula 5:
[0150] [Chemical formula 5]
[0151]
[0152] (F-1) a radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol
[0153] Use manufactured by BASF 944.
[0154] (F-2) Free radical scavenger with a molecular weight of 480
[0155] Use manufactured by BASF 770.
[0156] Characteristic evaluation
[0157] The impact resistance, heat resistance, and weather resistance of the samples for measuring physical properties according to Examples 1 to 4 and Comparative Examples 1 to 7 were measured in the following methods, and the evaluation results are shown in Table 2.
[0158] (1) Colorability: The lightness (L*) of a 2.5 mm thick sample was measured in the specular component exclusion (SEC) mode according to ASTM E308 by using CM-3700d manufactured by Konica Minolta Co., Ltd. The lower the lightness, the better the black color is achieved, which is judged to exhibit excellent colorability.
[0159] (2) Weathering resistance: The color change (ΔE) of the samples on the glossy surface was measured before and after irradiation with CM-3700d manufactured by Konica Minolta Co., Ltd. at an energy of 4,500 kJ, which was measured in accordance with SAE J 1960 by using a xenon arc accelerated weathering tester in the specular exclusion (SEC) mode.
[0160] (3) Scratch resistance: By using a scratch hardness tester 430P-I manufactured by Erichsen GmbH & Co. KG, 20 grid-like scratches were applied to the sample at intervals of 2 mm with a test tip having a diameter of 1 mm under a load of 10 N at a cutting speed of 1 m / min, and the lightness change (ΔL) of the sample before and after the scratches was measured, which was measured by using a CM-3700d manufactured by Konica Minolta in a specular reflection exclusion (SEC) mode. If a scratch is applied, microcracks appear on the surface of the sample, generating flaws, which increases the lightness of the sample, wherein the higher the lightness change (ΔL), the more damage is caused by the scratch, and the lower the scratch resistance.
[0161] (Table 2)
[0162]
[0163] Referring to the results of Tables 1 to 2, it was confirmed that the thermoplastic resin composition including components (A) to (F) and the molded article produced therefrom exhibited all of excellent colorability, weather resistance and scratch resistance.
[0164] While the invention has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments. On the contrary, the invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A thermoplastic resin composition comprising 100 parts by weight of the base resin comprising the following: (A) 10 to 15 wt % of an acrylic rubber-modified graft copolymer; (B) 10 to 30 wt% of a silicone-acrylate composite rubber-modified graft copolymer; and (C) 60 to 80 wt% of a polyalkyl (meth)acrylate resin, And based on the above base resin (D) 0.5 to 3 parts by weight of silicone-modified polyester; (E) 0.1 to 1 parts by weight of anthraquinone dye; and (F) 0.1 to 1 parts by weight of a radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol.
2. The thermoplastic resin composition according to claim 1, wherein (A) The acrylic rubber-modified graft copolymer includes a core comprising an acrylic ester rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylic ester compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
3. The thermoplastic resin composition according to claim 2, wherein The average particle size of the acrylic rubber polymer is 200 to 300 nm.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein (A) The acrylic rubber modified graft copolymer includes a butyl acrylate-styrene crosslinked copolymer core and a shell formed by grafting polymethyl methacrylate onto the core.
5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein (B) The silicone-acrylate composite rubber-modified graft copolymer includes a core comprising a silicone-acrylate composite rubber-like polymer, and a shell obtained by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
6. The thermoplastic resin composition according to claim 5, wherein The average particle size of the silicone-acrylate composite rubber-like polymer is 100-200 nm.
7. The thermoplastic resin composition according to any one of claims 1 to 6, wherein (B) The silicone-acrylate composite rubber-modified graft copolymer comprises an acrylate-silicone crosslinked copolymer core, and a shell obtained by grafting a styrene-acrylonitrile copolymer onto the core.
8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein (C) The polyalkyl (meth)acrylate resin is polymethyl methacrylate (PMMA) resin.
9. The thermoplastic resin composition according to any one of claims 1 to 8, wherein (D) The siloxane-modified polyester includes a structural unit represented by Chemical Formula 1: [Chemical formula 1] (in, In Chemical Formula 1, R 1 and R 6 are each independently hydrogen, hydroxy or methyl, R 2 , R 3 , R 4 and R 5 Each is independently a C1-C10 alkylene group, R 7 , R 8 , R 9 and R 10 are each independently a C1-C10 alkyl group or a C6-C20 aryl group, and m1, m2 and n are each independently an integer greater than or equal to 1).
10. The thermoplastic resin composition according to any one of claims 1 to 9, wherein (F) The radical scavenger having a weight average molecular weight greater than or equal to 2,000 g / mol includes a structure represented by Chemical Formula 2: [Chemical formula 2] (In Chemical Formula 2, m is an integer of 2 to 20).
11. The thermoplastic resin composition according to any one of claims 1 to 10, wherein The thermoplastic resin composition further includes at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, impact modifiers, lubricants, mold release agents, thermal stabilizers, antioxidants, ultraviolet (UV) stabilizers, pigments and dyes.
12. A molded product produced from the thermoplastic resin composition according to any one of claims 1 to 11.
13. The molded article according to claim 12, wherein The molded article has a lightness (L*) less than or equal to 2.0 as measured in specular excluded (SEC) mode according to ASTM E308 on a 2.5 mm thick sample.
14. The molded article of claim 12 or claim 13, wherein The molded article has a color change (ΔE) of less than or equal to 3.0 before and after a weathering test as measured by irradiating the molded article with an energy of 4,500 kJ according to SAE J 1960.
15. The molded article according to any one of claims 12 to 14, wherein The molded article has a lightness change (ΔL) of less than or equal to 2.0 before and after the scratch resistance evaluation, as measured using an Erichsen scratch hardness tester 430P-I.